Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Simplify [tex]\left(3a^4b^4c^5\right)^2 \left(2a^4b^4c^3\right)^3[/tex] completely.

[tex]\square[/tex]


Sagot :

To simplify the expression [tex]\(\left(3 a^4 b^4 c^5\right)^2\left(2 a^4 b^4 c^3\right)^3\)[/tex] completely, we will follow these steps:

### Step 1: Expand Each Part

First, we expand each part of the expression individually.

#### Part 1: Expand [tex]\(\left(3 a^4 b^4 c^5\right)^2\)[/tex]
Using the power rule [tex]\((xy)^n = x^n y^n\)[/tex]:

[tex]\[ \left(3 a^4 b^4 c^5\right)^2 = 3^2 \cdot (a^4)^2 \cdot (b^4)^2 \cdot (c^5)^2 \][/tex]

Calculate each component:
[tex]\[ 3^2 = 9 \][/tex]
[tex]\[ (a^4)^2 = a^{4 \cdot 2} = a^8 \][/tex]
[tex]\[ (b^4)^2 = b^{4 \cdot 2} = b^8 \][/tex]
[tex]\[ (c^5)^2 = c^{5 \cdot 2} = c^{10} \][/tex]

Thus, the expanded form is:
[tex]\[ \left(3 a^4 b^4 c^5\right)^2 = 9 a^8 b^8 c^{10} \][/tex]

#### Part 2: Expand [tex]\(\left(2 a^4 b^4 c^3\right)^3\)[/tex]
Using the power rule again:
[tex]\[ \left(2 a^4 b^4 c^3\right)^3 = 2^3 \cdot (a^4)^3 \cdot (b^4)^3 \cdot (c^3)^3 \][/tex]

Calculate each component:
[tex]\[ 2^3 = 8 \][/tex]
[tex]\[ (a^4)^3 = a^{4 \cdot 3} = a^{12} \][/tex]
[tex]\[ (b^4)^3 = b^{4 \cdot 3} = b^{12} \][/tex]
[tex]\[ (c^3)^3 = c^{3 \cdot 3} = c^9 \][/tex]

Thus, the expanded form is:
[tex]\[ \left(2 a^4 b^4 c^3\right)^3 = 8 a^{12} b^{12} c^9 \][/tex]

### Step 2: Multiply the Expanded Parts Together

Now, multiply the expanded parts together:
[tex]\[ 9 a^8 b^8 c^{10} \cdot 8 a^{12} b^{12} c^9 \][/tex]

First, multiply the numerical coefficients:
[tex]\[ 9 \cdot 8 = 72 \][/tex]

Next, multiply the variables with the same base using the rule [tex]\(a^m \cdot a^n = a^{m+n}\)[/tex]:
[tex]\[ a^8 \cdot a^{12} = a^{8+12} = a^{20} \][/tex]
[tex]\[ b^8 \cdot b^{12} = b^{8+12} = b^{20} \][/tex]
[tex]\[ c^{10} \cdot c^9 = c^{10+9} = c^{19} \][/tex]

### Final Simplified Expression

Combining all these results together, we get the completely simplified expression:
[tex]\[ 72 a^{20} b^{20} c^{19} \][/tex]

Therefore, the simplified expression is:
[tex]\[ \boxed{72 a^{20} b^{20} c^{19}} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.